CORRELATION BETWEEN CONFIDENCE AND PERFORMANCE OF ENGINEERING STUDENTS IN SOLID MENSURATION - Molina, Marivic G; Bansil, Alvin G (PEOPLE: International Journal of Social Sciences, 2018)
The study aimed to determine the correlation between the engineering students’ confidence and performance in solid mensuration. The respondents of the study were 144 first-year engineering students who were selected from six different engineering degree courses through stratified random sampling. Data were collected using the (1) Confidence Level Survey (CLS), and (2) Final Departmental Exam (FDE). The results revealed a significant positive correlation between confidence in mathematics and performance in solid mensuration. A significant positive correlation between confidence and performance in solid mensuration was likewise found. Concerning correlations between students’ confidence and performance in different learning competencies in solid mensuration, no significant correlation was found between confidence and performance in determining properties of solid figures. Likewise, no significant correlation was found between the confidence and performance in solving lateral surface area. Similarly, no significant correlation was detected between the confidence and performance in solving the total surface area. Meanwhile, a positive significant correlation was yielded between the confidence and performance in solving volume. Moreover, a significant positive correlation was found between the confidence and performance in solving the other parts of solid figures. No significant correlation, however, was found between the confidence and performance in solving applied problems involving solid figures. The study concluded that the more confident the students were, the higher their performances in solid mensuration were. Conversely, less confident students were not certain in their abilities, thus resulted in the low performance in solid mensuration. Study’s limitations and future scope were also discussed.